Transformasi Sistem Pangan dan Implikasinya Terhadap Kebijakan Ketahanan Pangan di Kota Semarang - Kurniawan, Hendra; Pradana, Arya; Khoirunnisa, Dianis Januar (Publikasi Penelitian Terapan dan Kebijakan, 2025)
Establishing a sustainable food system poses a significant challenge, particularly for policymakers. This study aims to identify the factors driving the transformation of the food system in Semarang City and to examine the integration of food security policies implemented to address these issues. A qualitative descriptive approach was employed, using the Grounded Theory Analysis method. Data were collected through document review and interviews with stakeholders. The findings reveal that the distribution sector has the highest weighted score for problems, followed by consumption, and then production. Quick Wins interventions, integrating cross-sectoral policies, were implemented to steer the existing food system towards greater sustainability. This research recommends the importance of enhancing institutional capacity through the formation of regional regulations and indicators for evaluating policy implementation. This ensures that the process of cross-sectoral policy integration, from formulation to evaluation, remains coherent in achieving stated objectives